BODY IMAGE DISTORTION: A STUDY WITH ADOLESCENTS - Perpiñá, Conxa; Baños, Rosa María (Anales de Psicología / Annals of Psychology)
Body image perception was measured in 83 young girls using a visual size apparatus. Those sample was divided on the basis of their "perceived weight", that is, those who thought they were under-weight; those who thought they were just the right weight; and those who thought of themselves as over-weight.Results showed that all subjects (except that group who perceived themselves as under-weight) over-estimated their weight. Moreover, we verified a tendency to the over-estimation in these groups, but this is more evident on the two groups that we far away of the "perceived slimness". We concluded that over-estimation of body size can be seen as a index of dissatisfaction with the own body, but this dissatisfaction rises of the perceived weight rather than the actual weight.